Penerapan Istishab dalam Penetapan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) Tentang Rahn Tasjily dan Rahn Emas - Muhammad Panca Prana Mustaqim Sinaga; Muhammad Mahendra Maskhur Sinaga; Zahra Malinda Putri; Salsabila Adinda Syarif; La Ode Mbunai (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Understanding the methods used by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) is important to be understood by the public in order to gain stronger confidence in the implementation of its fatwa. Of the various methods of determining law or ijtihad, one of the ones used by DSN-MUI is Istishab. The purpose of this study is to analyze the application of the Istishab ijtihad method in determining fatwas in DSN-MUI, especially fatwa on rahn tasjily and rahn emas. The research method used uses a Qualitative method with a normative juridical approach that uses secondary and analytical descriptive data as the data analysis technique used. The results of this study state that one of the legal sources used by DSN-MUI in formulating its fatwa is istishab. In general, in the application of istishab in its fatwa, DSN-MUI in most of its fatwas uses the rules derived from isitishab in the form of the law of origin of muamalat is permissible. However, there are two fatwas that clearly show the use of istishab in the issuance of fatwa, namely in Fatwa D about Rahn Emas and Rahn Tasjily. In both fatwas, the elements that become the harmony and conditions in the use of istishab as a legal evidence have been fulfilled, both of which are related to rahn in general that have taken place in the past, which then these postulates are used to determine the applicability of the rahn law in the present time which is used in the form of golden rahn and rahn tasjily. In addition, it also uses derivative rules from istihab itself in the form of the basic law of muamalat, which is permissible until there is evidence that supports it.